Humanistic Governance in Democratic Organizations The Cooperative Difference - Novković, Sonja; Miner, Karen; McMahon, Cian (Humanism in Business Series,, 2023)
This open access edited book brings together a number of theories under the umbrella of humanistic governance to develop a persuasive alternative perspective on governance, particularly for democratic organisations such as co-operatives. It examines how we can move beyond a profit-first approach to governance, into a framework that prioritises human dignity in all aspects of an operation. This book also discusses key issues for different types of cooperatives and how these might be addressed. And, finally, it addresses how cooperatives can better cope with dynamic change processes. This book will be of interest for academics working in the areas of stakeholder governance, social solidarity economy, ethical management and co-operatives. Sonja Novkovic is a Professor of Economics and Academic Director of the International Centre for Co-operative Management at Saint Mary's University in Halifax, Canada. She is a member and former Chair of the International Cooperative Alliance Research Committee. Karen Miner is the Managing Director and a Governance Researcher for the International Centre for Co-operative Management at Saint Mary's University, Canada. Cian McMahon is a Postdoctoral Research Fellow with the International Centre for Co-operative Management at Saint Mary's University, Halifax, Canada. He has published in the fields of economic democracy, community development, heterodox economics, and economic inequality.